Character Education Based On The Quran Surat Al-Nahal Verse 125 - Roimun Roimun; Iis Faridah; Sujai Sujai (L, 2022)
The Qur'an is part of the guideline for human life, therefore, later it will deliver to Allah who created all living things and their contents. Education is the foundation for the nation's children who will humanize humans. Character is human nature that already exists in the human soul, but the character is affected by every situation if it is not directed as well as possible. Thus, character education in the Qur'an is a unified whole that is inherent in humans. Every behavior makes him influenced and controlled when that character always adheres to the teachings of Allah, namely the Al-Quran and Al-Hadith. education that will open children's character and part of the gate of knowledge, therefore, the starting point of the ocean of knowledge and values is that we teach the Koran and the value of character education to them, so that in the future they will become warriors of justice, community leaders and scientists. This research is focused on analyzing several research objects, which are books related to Character Education Based on Al-Quran Surat An-Nahal 125